2000
DOI: 10.1023/a:1008905229522
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The corrosion of five materials for implant suprastructures (cast-titanium, machined-titanium, gold alloy, silver-palladium alloy and chromium-nickel alloy), was investigated in vitro, the materials being galvanically coupled to a titanium implant. Various electrochemical parameters E(CORR), i(CORR) Evans diagrams, polarization resistance and Tafel slopes) were analyzed. The microstructure of the different dental materials was observed before and after corrosion processes by optical and electron microscopy. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Palladium-based alloys without silver show a rather passive behaviour and better than the Pd-Ag alloys [12]. Similarly, Cortada [9], in a galvanic corrosion study, concluded that palladium–based alloys present low levels of ions release in combination with titanium. In addition, it was shown that resistance to corrosion in silver–palladium based alloys is compatible with alloys with high contents of gold studied in artificial saliva [3, 5, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palladium-based alloys without silver show a rather passive behaviour and better than the Pd-Ag alloys [12]. Similarly, Cortada [9], in a galvanic corrosion study, concluded that palladium–based alloys present low levels of ions release in combination with titanium. In addition, it was shown that resistance to corrosion in silver–palladium based alloys is compatible with alloys with high contents of gold studied in artificial saliva [3, 5, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Electro-chemical corrosion is the most important injury factor in dental work. It produces unintended wear of the metal surface, and a deterioration of the outer and inner layers caused by exposure to chemicals or electrochemical reaction of the surrounding area [9]. …”
Section: Introductionmentioning
confidence: 99%
“…But recently, the biostability of titanium is increasingly questioned. Corrosion products in inner organs5 and galvanic side effects6 have been reported while using titanium implants. And allergic reactions and sensitivities to titanium have been also reported 7.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys have been used broadly and successfully for numerous applications such as sport equipment [1], aerospace industry [2], marine application [3], medical applications [4] because of its optimum mechanical properties, outstanding corrosion resistance and bio-inert due to the presence of a thin layer of titanium oxide which a naturally formed onto the titanium surface [5][6]. This layer mainly consists of titanium dioxide or titania.…”
Section: Introductionmentioning
confidence: 99%